Iñupiat of the Sii: historical ethnography and Arctic challenges - Anderson, Wanni W., author; Anderson, Douglas D., author; University of Alaska Press, publisher (Colorado State University. Libraries, 2024)
First-hand account of the authors' lived experiences and archaeological and ethnographic research during eight field seasons in Selawik, Alaska, from 1968 to 1994, including historical and archaeological data representing the early periods of Selawik village.--Provided by publisher.
Prologue: Riverine Village by the Sii -- Part 1: Early times -- Introduction -- History before the village years -- Founding of Selawik village -- Trade fair with Indians -- Fur trade and early trading posts in Selawik -- Introduction of reindeer herding -- Part 2: Through the ethnographic lens, Selawik from the 1970s -- The long, cold winter -- Long days and the summer rhythm -- The Selawik wolves and the Maklak telegraph -- From modernity to self-determination.
Keywords: Native Village of Selawik -- Social life and customs; Native Village of Selawik -- History; Inupiat -- Native Village of Selawik -- Social life and customs; Inupiat -- Native Village of Selawik -- History; Excavations (Archaeology) -- Native Village of Selawik